Isle of Man : Crown Dependency of the United Kingdom; Assessment of the Supervision and Regulation of the Financial Sector Volume II-Detailed Assessment of Observance of Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2003)
This assessment of the Basel Core Principles for Effective Banking Supervision has been completed as part of the IMF Offshore Financial Center (OFC) assessment program. First, the assessment benchmarks the current state of banking supervision, recognizing that there have been extensive changes in the last few years. Second, it suggests a number of further improvements or changes. Thus, this report provides a key input for the development of an action plan to move toward full compliance with the Core Principles.